THE USE OF WATTPAD IN ENGLISH LANGUAGE TEACHING AND LEARNING: IS IT HELPFUL? - Nurus Syamsiyah Furotun; Mutmainnah Mustofa; Erfan Efendi; Nur Jamilah (Journal of English for Academic and Specific Purposes)
The use of digital applications is very helpful in teaching and learning process, especially for language classes. The existence of technology is very helpful for teachers to increase student interest in learning about English language lesson. The development of the digital world is used by teachers to be used as a tool to facilitate student learning. This research focuses on the role of using a digital application called Wattpad which will make students diligently read English reading texts, so that they become more skilled in learning. In this research, the researchers defined the term digital application to explain the use of digital application in an effort to improve English as a foreign language learning skill. The related review of literature shows that the use of multi-media technology can improve students’ language learning skills because matches their interests. Therefore, their English skills can be better.